Practical Decision Algorithms for the Use of the Cardiovascular Polypill in Secondary Prevention in Europe - Grigorian-Shamagian, Lilian; Edel, Klaus; Esteve-Pastor, María Asunción; Aceña, Álvaro; Silva, Claudia; Delgado-Silva, Joana; Ntaios, Georges; Demerouti, Eftychia; Brotons, Carlos (Frontiers in Cardiovascular Medicine, 2021)
The main objective of cardiovascular disease (CVD) prevention is to reduce morbidity and mortality. Despite recommendations on evidence-based pharmacological treatment and lifestyle changes, the control of CV risk factors such as hypertension or dyslipidaemia is not optimal. The use of a CV polypill, including guideline-recommended drugs, as a baseline therapy, may contribute to improving risk factors control either by improving the treatment adherence or by the synergistic effect of its components. The CNIC-Polypill is the first CV polypill approved in Europe as an effective strategy for secondary prevention, which contains acetylsalicylic acid, atorvastatin (in two optional doses), and ramipril (in three optional doses) in a single pill. The present practical clinical document aims to provide a guide for patient management after an acute coronary syndrome (ACS) or with chronic CVD (CCVD) with a strategy based on the CNIC-Polypill, also considering the need to add other therapies for a personalized treatment. The most suitable clinical scenarios for the CNIC-Polypill use are discussed: (a) in patients after an ACS at discharge, (b) in patients with CCVD (chronic coronary syndrome, stroke, or peripheral artery disease) with uncontrolled low-density lipoprotein cholesterol (LDL-c) and/or blood pressure levels and (c) in patients with CCVD with well-controlled risk factors to simplify treatment and reduce polypharmacy in the context of CCVD prevention.